Implementation of the 7e Learning Cycle setting Peer Learning Learning Model to Improve Student Learning Outcomes: Penerapan Model Pembelajaran Learning Cycle 7e setting Peer Learning Untuk Meningkatkan Hasil Belajar Siswa - Desi Yunita Putri; Arie Ramadhani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to improve the learning outcomes of VII class sttudent the subjects of Pancasila and Citizenship Education through the application of the Learning Cycle 7e learning model in a Peer Learning setting. The type of research used is Classroom Action Research (PTK). In this research, it was carried out in two cycles and consisted of several stages, namely introduction or planning, action implementation, observation and reflection. The material used in this research is about cooperation in various fields of life. The subjects in this research were class VII students consisting of 28 students. Data collection techniques include tests, observation, interviews and documentation. The results of this research are that by implementing the Learning Cycle 7e learning model in the Peer Learning setting, it can improve student learning outcomes starting from pre-action, cycle I and cycle II. In the pre-action, the average value of learning outcomes was 62.2, then in cycle I there was an increase in the average value of learning outcomes to 82.4 and in cycle II there was an increase in learning outcomes of 93.6. The conclusion of this research is that the application of the Learning Cycle 7e learning model setting Peer Learning can improve learning outcomes in Pancasila and Citizenship Education subjects on cooperation material in various areas of life in Class VII MTs.